Principal Component Analysis of Morphometric Traits and Their Association With Body Weight in Indigenous Kacang Goats of Binongko Island, Southeast Sulawesi - Rahadi, Syam; Irawati; Sandiah, Natsir; Rusdin, Muh. (Jurnal Ilmu-Ilmu Peternakan, 2026)
Kacang goats represent one of Indonesia’s native genetic livestock resources and are widely recognized for their ability to thrive in harsh tropical conditions. Understanding body conformation traits and their association with live weight is important for improving breeding strategies and herd management. This research was conducted to describe the morphometric characteristics of adult Kacang goats reared on Binongko Island, Southeast Sulawesi, examine the association between body dimensions and body weight, formulate body weight prediction equations, and determine major sources of phenotypic variation through Principal Component Analysis (PCA). A total of 259 adult Kacang goats, comprising 117 bucks and 142 does, maintained under extensive production systems, were evaluated. Measurements recorded included body weight (BW), body length (BL), withers height (WH), chest girth (CG), chest depth (CD), chest width (CW), and rump height (RH). Data analysis involved descriptive statistics, Pearson correlation coefficients, regression analysis, and PCA. The findings demonstrated that body weight was positively and significantly associated with all measured body dimensions (p < 0.01). The highest correlation in males was between BW and WH (r = 0.741), and in does, between BW and CD (r = 0.675). The best regression models were obtained from CG and WH in bucks (R² = 0.560) and from BL, CD, and CW in does (R² = 0.509). PCA revealed that overall body size explained most of the morphometric variation, accounting for 84.91% in bucks and 89.86% in does, with BL, WH, CG, and RH identified as the most representative morphometric traits.